2020
DOI: 10.1177/1523422319886297
|View full text |Cite
|
Sign up to set email alerts
|

Technology Intervention: Rethinking the Role of Education and Faculty in the Transformative Digital Environment

Abstract: The Problem Technology has affected almost every aspect of our lives, including education. Higher education is shifting the dynamics of delivery methods from traditional face-to-face to online to blended modes. Many universities are reaching a physical space capacity and therefore are attempting to increase online enrollment and geographical footprint. These changes are shifting the nature of higher education and how faculty are being viewed, evaluated, and, to some degree, hired. This article will focus on hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…In the digital era of knowledge economy, higher education plays a more critical role than ever. Competence in terms of both human capital and advanced technology have transformed education for the good of society (Rosenbusch, 2020). Today, the welfare of society depends more on intangible assets rather than tangible resources.…”
Section: Introductionmentioning
confidence: 99%
“…In the digital era of knowledge economy, higher education plays a more critical role than ever. Competence in terms of both human capital and advanced technology have transformed education for the good of society (Rosenbusch, 2020). Today, the welfare of society depends more on intangible assets rather than tangible resources.…”
Section: Introductionmentioning
confidence: 99%
“…In today's ubiquitous technological and digital environment, Higher Education Institutes are providing the opportunity of Machine Learning (ML) to software engineering, computer science, business-oriented students, and other education-related degree programs. (Kann, 1983) stated that the purpose of Machine learning is to train computers with the help of Artificial Intelligence to follow patterns to predict some behavior or circumstance or to detect some phenomenon (Rosenbusch, 2020). Many higher education institutes have administered strong network routes which also provides added advantage to the management of the educational institutes in terms of managing all academic activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Virtual learning environments are often designed as applications in which people and digital objects integrate into one system, which is known as Webbing In . In this environment, digital items such as online learning environments, 3 D virtual worlds and serious games and virtual reality/mixed reality are considered as parts of the virtual environment, all of which are used as tools to enhance learning in VHRD environments (Bennett, 2014b, Li, 2016; Khandelwal and Upadhyay, 2019; and Rosenbusch, 2020). Previous studies indicated that employees get more engaged in virtual learning environments when learning tools such as VSP are used in VHRD processes.…”
Section: Descriptive Analysis Of Virtual Human Resources Development ...mentioning
confidence: 99%